Destroying synchrony in an array of the FitzHugh–Nagumo oscillators by external DC voltage source - Adomaitienė, Elena; Bumelienė, Skaidra; Mykolaitis, Gytis; Tamaševičius, Arūnas (Nonlinear Analysis: Modelling and Control, 2020)
A control method for desynchronizing an array of mean-field coupled FitzHugh–Nagumo-type oscillators is described. The technique is based on applying an adjustable DC voltage source to the coupling node. Both, numerical solution of corresponding nonlinear differential equations and hardware experiments with a nonlinear electrical circuit have been performed.
Keywords: coupled oscillators; FitzHugh–Nagumo oscillators; synchronization